Decentering the Center in D H Lawrence's 'Tickets Please!' - Shrestha, Jivan (Patan Prospective Journal, 2023)
This research delves into D.H. Lawrence's short story, 'Tickets Please!' employing a poststructuralist and deconstructionist framework to unravel the narrative's layers of meaning. The study addresses a notable gap in existing literature by emphasizing the decentering approach within the context of the story's exploration of gender roles during the transitional wartime period. The research problem prompts an investigation into how Lawrence's story challenges and subverts the established hierarchies, especially those related to gender roles, and how this aligns with the deconstructive tenets proposed by Derrida. The literature review critiques previous analyses, revealing a lack of attention to the deconstructionist perspective. Scholars have often examined aspects such as narration, characterization, and feminist stylistic elements but have neglected the narrative's pivotal decent ring theme. The story unfolds symbolically, tracing the shift from structuralism to poststructuralist through the metaphor of tramcars. These tramcars represent the destabilization of traditional patriarchal structures, marking a rupture in societal norms. The absence of the male center and the emergence of assertive female roles illustrate a transformative moment during wartime. Characters like John Joseph and Annie embody the clash between remnants of patriarchal norms and the evolving alternative center, personifying the narrative's overarching decentering theme. The narrative challenges binary oppositions and questions the concept of a fixed center, offering a multifaceted exploration of societal shifts.